Microelectronics, Electromagnetics and Telecommunications Proceedings of the Fourth ICMEET 2018 - Panda, Ganapati; Satapathy, Suresh Chandra; Biswal, Birendra; Bansal, Ramesh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book discusses the latest developments and outlines future trends in the fields of microelectronics, electromagnetics and telecommunication. It contains original research works presented at the International Conference on Microelectronics, Electromagnetics and Telecommunication (ICMEET 2018), organised by GVP College of Engineering (A), Andhra Pradesh, India. The respective papers were written by scientists, research scholars and practitioners from leading universities, engineering colleges and R&D institutes from all over the world, and share the latest breakthroughs in and promising solutions to the most important issues facing today's society.
Hand Gesture Based Quadcopter -- Robotic Flexible Artificial Finger Design Using Nano-Sized DC Motors and Gears for Finger Injuries -- A Novel and Efficient Design for Squaring Units by Quantum-Dot Cellular Automata -- Optimal Forwarding in Named Data Networking -- A Spatial and Spectral Feature-based Approach for Classification of Crops using Techniques based on GLCM and SVM -- Lisp Detection and Correction Based on Feature Extraction and random Forest Classifier -- NLMS-LOSES Algorithm for Adaptive Noise Cancellation -- Application of Generalized Constrained Neural Network with Linear Priors to Design Microstrip Patch Antenna -- Dual Band MIMO Antenna with Reduced Mutual Coupling Using DGS -- Nonlinear Signal Processing Applications of Variants of Particle Filter: A Survey -- Evaluating the effectiveness of Visual Techniques Methodologies for Cerebral Palsy Children and Analyzing the Global Development Delay -- Design of Dual-Band MIMO Antenna for LTE 2500, Wimax and C-Band Applications to Reduce the Manual Coupling -- A Hybrid Alzheimer's Stage Classifier by Kernel SVM, MLP Using Texture and Statistical Features of Brain MRI -- MEMS Sensor Based Cantilever for Intracranial Pressure Measurement -- Quad Bio-MEMS Disease Detector (QBDD).
Keywords: Electronics; Electronic circuits; Telecommunication; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Systems; Communications Engineering, Networks